Visual culture studies - Smith, Marquard; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2008)
This collection comprises interviews with an array of influential American and European intellectuals from across the arts, humanities, and social sciences working today on visual culture within the university context and beyond.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Culture; Visual communication; Art and society; Visual perception; Electronic books